INTERPRETATION OF BOUGUER ANOMALY TO DETERMINE FAULT AND SUBSURFACE STRUCTURE AT BLAWAN-IJEN GEOTHERMAL AREA - Azhari, Anjar Pranggawan; Maryanto, Sukir; Rachmansyah, Arief (Department of Physics, Maulana Malik Ibrahim State Islamic University of Malang, 2016)
Gravity survey has been acquired by Gravimeter Lacoste Romberg G-1035 at Blawan-Ijen geothermal area. It was a focusing study from previous research. The residual Bouguer anomaly data was obtain after applying gravity data reduction, reduction to horizontal plane, and upward continuation. Result of Bouguer anomaly interpretation shows occurrence of new faults and their relative movement. Blawan fault (F1), F2, F3, and F6 are normal fault. Blawan fault is main fault controlling hot springs at Blawan-Ijen geothermal area. F4 and F5 are oblique fault and forming a graben at Banyupahit River. F7 is reverse fault. Subsurface model shows that Blawan-Ijen geothermal area was dominated by the Ijen caldera forming ignimbrite (Ï1=2.670 g/cm3), embedded shale and sand (Ï2=2.644 g/cm3) as Blawan lake sediments, magma intrusion (Ï3=2.814 g/cm3 Ï7=2.821 g/cm3), andesite rock (Ï4=2.448 g/cm3) as geothermal reservoir, pyroclastic air fall deposits (Ï5=2.613 g/cm3) from Mt. Blau, and lava flow (Ï6=2.890 g/cm3).